SACRED SPACE IN THE NATIONAL MUSIC OF THE STEPPE PEOPLES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the phenomenon of sacred space in the traditional musical culture of the Kazakh people. It analyzes the mythological, ritual, and natural aspects that shape sacred musical space, focusing on the symbolic meanings of the kobyz and the legend of Korkyt and his she-camel Zhelmaya. Special attention is paid to sound as a mediator between material and spiritual worlds, and to the role of musical ritual in preserving cultural memory. The methodology draws from ethnomusicology, sound phenomenology, and cultural anthropology. The findings highlight the spiritual significance of Kazakh traditional music and its relevance to the preservation of intangible cultural heritage.
Keywords: kazakh culture, sacred space, kobyz, Korkyt, traditional music, ritual, intangible heritage